STRATEGI DAKWAH DALAM MENINGKATKAN SUMBER DAYA MANUSIA YANG PROFESIONAL DAN BERAKHLAKUL KARIMAH: PENDEKATAN KONSEPTUAL DAN EMPIRIS - Aris Fachrizal, Muhammad; Herdi; Hartono; Kadarusman, Adang; Sobirin (CV SWA Anugerah, 2024)
This study aims to evaluate the implementation of da’wah strategies in enhancing professional and morally virtuous human resources through a community engagement approach. The research adopts a descriptive qualitative method with data collected through participatory observation, in-depth interviews, and documentation. The findings reveal that contextual and participatory da’wah strategies, combined with empowerment programs, effectively improve participants' professional competencies through skill training, reinforcement of Islamic work ethics, and digital literacy. Furthermore, moral values such as honesty, discipline, responsibility, and social care were successfully internalized and applied in daily life. The utilization of digital technology has expanded the reach of da’wah, although challenges such as low digital literacy and resistance to modern methods remain. This study highlights the importance of collaboration among religious leaders, educational institutions, and government bodies to support the sustainability of structured and adaptive da’wah programs. With appropriate strategies, da’wah can play a significant role in creating a generation that is professional, competitive, and morally virtuous in accordance with Islamic values. Keywords: Da’wah, Professionalism, Akhlakul Karimah, Human Resources, Community Engagement